Neural mechanisms underlying visuomotor learning : interacting cortical systems - Roche, Richard A. P. (Trinity College (Dublin, Ireland). School of Psychology, 2003)
Introduction: We are the products of our experiences. Every sight, sound and smell, every event, encounter and exchange, all leave their indelible mark on the way we act, think and feel. The things we learn from our experiences stay with us, they allow us to better understand the nature of our world, to reveal connections that were once veiled. Learning arms us with the knowledge to make better choices, steers us to take one path over another, lights our way and helps us find solid ground for our footfalls. We can see a distance into the future because we stand, not on the shoulders of giants, but atop a mound of bones, the bones of experiences past. Through learning, how we react in different situations will be informed; one course among a multitude of possible actions will seem preferable. Learning occurs in the brain. Despite his harsh and disdainful view, Butler’s conception of learning as a "cobweb of the brain" is startlingly apt. The complex web of learning that is spun by experience into ever more intricate patterns mirrors the intermingling branches of the brain's structure as it grows and connects, moulded and guided by experience. This thesis is concerned with learning: what happens in the brain when we learn, how this learning takes place and how what we have learned can be used to influence our complex behaviours.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin